2013
DOI: 10.1111/jfr3.12016
|View full text |Cite
|
Sign up to set email alerts
|

Optimal prioritisation of watershed management measures for flood risk mitigation on a watershed scale

Abstract: Watershed management includes methods to create, enhance, and maintain vegetation to reduce run‐off and provide flood control in the watershed. The assignment of priority for watershed management measures requires the use of mathematical techniques to attain the most suitable strategies. In the present study, a framework was presented for assigning the optimal combinations of watershed management measures based on simulation‐based optimisation approach. For this purpose, a one‐dimensional hydrodynamic model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Step gives the relationship between damage percentile and flood depth (Corry et al 1980, Messner et al 2007Olesen et al 2017;Wobus et al 2017;Jamali et l. 2018). They are prepared for different land uses of the Kan river basin (WRI 2011a; Yazdi et al 2013). This method has been developed by the Federal Emergency Management Administration (Berkman and Brown 2015).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Step gives the relationship between damage percentile and flood depth (Corry et al 1980, Messner et al 2007Olesen et al 2017;Wobus et al 2017;Jamali et l. 2018). They are prepared for different land uses of the Kan river basin (WRI 2011a; Yazdi et al 2013). This method has been developed by the Federal Emergency Management Administration (Berkman and Brown 2015).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Kan River basin is one of the most important flooding basins located in the north of Tehran city and a vulnerable area against flood (WRI 2011a; Yazdi and Salehi Neyshabouri 2012;Yazdi et al 2013). It is reported that in the flood of July 15, 2015 a https://doi.org/10.5194/nhess-2019-166 Preprint.…”
Section: Study Areamentioning
confidence: 99%
“…Nevertheless, study show that it was necessary to ensure that the assessment factors and weights fit the purpose of the project to be carried out. Zhou et al [11] analyzed whether the diversification of the measures has an impact on reducing flood damages Yazdi et al [12] applied an optimization method based on a simulation when selecting the measures for a basin, and the optimal size of the combination was calculated by applying the Pareto method to compose combinations. The research shows that economically efficient measures can be selected by using the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually they provided trade-off curves between pollutant reduction and total cost increase. Yazdi et al (2013) obtained optimal prioritisation of watershed management for flood risk mitigation on a watershed scale. They used a mathematical model to minimise the flood damages and total costs of watershed management measures.…”
Section: Introductionmentioning
confidence: 99%